Chest Wall Masculinization in Female-to-Male Transsexuals: Our Treatment Algorithm and Life Satisfaction Questionnaire. Issue 6 (December 2019) - Morselli, Paolo G.; Summo, Valeria; Pinto, Valentina; Fabbri, Erich; Meriggiola, Maria C.
Abstract : Abstract: Esthetic masculinization of the chest wall is one of the first surgical steps in female-to-male transsexual (FTMTS) reassignment. This surgical procedure is not a simple mastectomy: it is required for removal of breast tissue with glandular resection and skin excess revision, to reduce and replace the nipple-areola complex in the right location, minimizing chest wall scars. The creation of an esthetically pleasing male chest allows the patient to live at ease in the male gender role. In this article, we present our series of 68 FTMTSs who underwent bilateral mastectomies for surgical sexual reassignment (a total of 136 mastectomies) according to our algorithm, in the period between January 2010 and December 2017. We selected 4 different operative procedures, classified as subcutaneous ("pull-through" and "concentric circular" techniques) and skin extended ("ultrathin vertical bipedicle" and free nipple graft). We achieved a total complication rate of 6.6%, less than that reported in the literature; additional procedures for esthetic improvements were performed in 14.7% of cases. The mean patient satisfaction was approximately 4.57% of a maximal value of 5 (excellent). To help surgeons in choosing the most appropriate FTMTS surgical technique and to reduce unfavorable results, we propose the use of our treatment algorithm in preoperative evaluation of the chest wall according to the breast volume, degree of glandular ptosis, and skin elasticity.